(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Ponomarenko T. V. Independence is an important component of art conducting of future music teachers. The author considers the possibility of achieving the quality of the temple in the art of conducting, not only obtained in the learning process in higher education of theoretical and practical skills, but also due to work independently.